Acute Brain Imaging in Children: Can MRI Replace CT as a Screening Tool?. Issue 1 (30th October 2015) - Wagner, Matthias W.; Kontzialis, Marinos; Seeburg, Daniel; Stern, Steven E.; Oshmyansky, Alexander; Poretti, Andrea; Huisman, Thierry A.G.M.
ABSTRACT: BACKGROUND AND PURPOSE: To determine if axial T2‐weighted imaging can serve as screening tool for pediatric brain imaging. METHODS: We retrospectively evaluated consecutive brain magnetic resonance imaging (MRI) data of 161 children (74 girls) with a mean age of 7.44 ± 5.71 years. Standard of reference was the final report of neuroradiology attendings. Three readers with different levels of experience were blinded for clinical diagnoses and study indications. First, readers studied only the axial T2‐weighted screening sequence. Second, they studied all available anatomical and functional MRI sequences as performed per standard protocol for each clinical indication. The readings were classified as normal or abnormal. Sensitivity and specificity were measured. RESULTS: Axial T2 screening yielded a sensitivity of 77‐88% and a specificity of 92%. The full studies/data sets had a sensitivity of 89‐95% and a specificity of 86‐93%. Nineteen of 167 studies were acquired for acute and 148 of 167 studies for nonacute clinical indication. Twenty‐five false‐negative diagnoses paneled in three groups were made by all readers together. Readers misread four of 19 studies with acute and 21 of 148 studies with nonacute clinical indication. Four of 21 misread studies with nonacute indications harbored unexpected findings needing management. CONCLUSIONS: Axial T2 screening can detect pediatric brain abnormalities with high sensitivity and specificity and can possibly replace CT as screening tool if the reading physician is aware of possible limitations/pitfalls. The level of experience influences sensitivity and specificity. Adding diffusion‐weighted imaging and susceptibility‐weighted imaging to a 3‐dimensional T2‐weighted sequence would most likely further increase sensitivity and specificity.